Records management practices in ecumenical tertiary institutions: the Trinity Theological Seminary in focus - Narh Akuffo , Maxwell; Adams , Musah (Archives & Manuscripts, 2016)
The study aimed at examining the records management practices at the Trinity Theological Seminary in Ghana and was underpinned by the life cycle concept. The researchers drew qualitative inferences from interviews, complementing personal observations, with 25 purposively sampled staff. The study revealed the creation, maintenance and use of records to support administrative and decision-making processes. Problems hampering effective records management included non-existent records management policy, inadequate staff training and erratic power supply. Among the recommendations proposed to overcome these setbacks were: formulating a written policy statement for managing records, providing staff with formal training and installing a standby generator.